Forced to Concede: Permanent Restructuring and Labour's Place in the North American Auto Industry - Siemiatycki, Elliot (Antipode, 2012)
The stunning decline of Ford, General Motors and Chrysler over the past decade has rendered the once 'Big Three' US automakers a vulnerable 'Detroit Three'. In their attempts to return to profitability, the Detroit Three have undertaken a series of 'turnarounds' aimed at renewing their competitive edge. Through this corporate restructuring agenda, 250,000 assembly jobs in North America have been lost, upwards of 50 auto plants have been closed, wages and benefits for new hires have been cut substantially and once strong, independent auto unions have been thoroughly overwhelmed. Permanent restructuring, then, represents a crisis strategy on the part of the corporate elite to continually intensify the demands placed on labour in the hopes of creating new conditions for capital accumulation. Working within labour geography, this paper documents the 'regional race to the bottom' in the North American auto industry while reminding labour geographers that capitalist restructuring is a powerful constraint on labour agency.
Keywords: AUTOMOBILE industry; BUSINESS enterprises – United States; CHRYSLER Corp.; CORPORATE reorganizations; EMPLOYEES – Dismissal of; FORD Motor Co. Ltd.; GENERAL Motors Corp.; United States